Catalyst Role of Covid 19 Pandemic in Increasing Adoption of Over-the-Top (OTT) Platforms- A Study Conducted amongst Gen Z of Guwahati City, Assam - Dikshya Saikia; Gaurav Nirmal (International Journal of Engineering and Management Research, 2022)
The outbreak of Covid 19 has drastically increased the use of viewership in multiple OTT platforms. OTT platforms are media service providers, providing users with direct access to the different forms of content over the internet doing away with the need for connection to a dedicated carrier. Different age grouped people with diverse requirement of media need has been provided with the option to subscribe to OTT services. The present study has been conducted with the purpose to assess the factors affecting on-demand content popularity among users of the selected study area i.e. Guwahati city in contrast to pre-established platforms; with special reference to the pandemic. The results have shown a positive trend on the use of OTT services during the covid pandemic and it can be said that Covid 19 pandemic has definitely acted as a catalyst in increasing adoption of OTT services amongst Generation Z of Guwahati city with almost 60% respondents stating that they have started using OTT after the pandemic.